Perspectives on Marital Dissolution Divorce Biographies in Singapore - Quah, Sharon Ee Ling. (Springer Singapore : Imprint: Springer, 2015)
This book presents a sociological account on marital dissolution that engages and extends theorisations on individualisation and the contemporary organisation of personal relationships to discuss how the experience of divorce might not be all debilitating but on the contrary, could provide opportunities for productivity, self-responsibility and relationship formation. Using Singaporean divorcees’ narrative accounts, the book explores how divorcees shape and construct what the author refers to as, a divorce biography, to end their unsatisfying marriages, cope with the crisis, negotiate the associated risks, organise post-divorce personal communities and make future plans. It uncovers how divorcees navigate their divorce biographies within the economic, policy and social context they are located in and examines the conditions that facilitate or hinder the pursuit of productivity in different facets of their post-divorce lives. Far from a standard story of divorce, this book presents the diversity and complexity of Singaporean divorce biographies. The research challenges negative discourses associated with divorce and offers a more nuanced perspective by discussing both the precarious and productive aspects of the experience. More importantly, it provides a critical discussion on the limited definition of family prevalent in Singaporean society, and shows how post-divorce family life and practices continue to thrive despite the rupture of marriage.